The foreign medical graduate: a bibliography. (DHEW publication ;, 1972)
About 400 references to journal articles, government documents, and miscellaneous publications through Sept., 1972, about the foreign medical graduate in the United States. Alphabetical arrangement by authors. Entries include bibliographical information and indexing terms. KWIC, source indexes.